Human antibody recognition of xenogeneic antigens (NeuGc and Gal) on porcine heart valves: could genetically modified pig heart valves reduce structural valve deterioration?. (11th August 2016) - Lee, Whayoung; Long, Cassandra; Ramsoondar, Jagdeece; Ayares, David; Cooper, David K. C.; Manji, Rizwan A.; Hara, Hidetaka
Abstract: Background: Glutaraldehyde‐fixed bioprosthetic heart valves (GBHVs) derived from wild‐type (WT, genetically unmodified) pigs are widely used clinically for heart valve replacement. There is evidence that their failure is related to an immune response. The use of valves from genetically engineered pigs that do not express specific pig antigens may prolong GBHV survival. Our aims were to determine (i) expression of Gal and NeuGc on heart (aortic and pulmonary) valves and pericardium of WT, α1, 3‐galactosyltransferase gene knockout (GTKO) and GTKO/ N ‐glycolylneuraminic acid gene‐knockout (GTKO/NeuGcKO) pigs in comparison with three different commercially available GBHVs and (ii) to determine human antibody binding to these tissues. Methods: Wild‐type, GTKO/CD46, and GTKO/CD46/NeuGcKO pig valves and pericardium were tested (i) fresh and (ii) after fixation with glutaraldehyde (0.02%, 0.2%, 2%). Sections of GBHVs, fresh and fixed valves, and pericardium were stained for Gal and NeuGc expression, and for human IgM and IgG antibody binding. Results: Gal and NeuGc expression was high on all GBHVs and WT pig valves/pericardium, but was absent after antigen‐specific‐knockout. There was no difference in antigen expression or antibody binding among WT aortic, pulmonary valves, and pericardium as well as GBHVs. Glutaraldehyde fixation did not alter expression of Gal or NeuGc. After incubation with human serum, human IgM and IgG bound to all GBHVs and WT pig valves/pericardium. Valves from GTKO/CD46 pigs and, particularly, GTKO/CD46/NeuGcKO pigs (with/without glutaraldehyde fixation) showed less IgM and IgG binding. Conclusion: Compared to WT pigs, GTKO/CD46/NeuGcKO pigs would be preferable sources of GBHVs, because the absence of Gal/NeuGc expression reduces human antibody binding.